Amazonian Discovery Sheds Light on the Evolution of Caenocentron Schmid, 1982 (Trichoptera: Xiphocentronidae): Phylogenetic Placement and Description of a New Species - Desidério, Gleison R. [UNESP]; Vilarino, Albane; Santos, Laissa da Silva dos; Bispo, Pitágoras C. [UNESP]; Hamada, Neusa (MDPI, 2025)
Caenocentron was previously hypothesized to have originated in Mesoamerica from Xiphocentronidae ancestors that dispersed from Asia to the Americas during Eocene hyperthermal events. Under this scenario, the genus underwent early diversification in Mesoamerica and reached South America only during the late Miocene, following the uplift and connection of Central America. However, the discovery of Caenocentron roosevelt sp. nov. in savanna areas of the Brazilian Amazon significantly revises this understanding. A morphology-based parsimony analysis of Caenocentron and related xiphocentronids (26 taxa, 46 characters) recovered C. roosevelt sp. nov. as the sister species to all other members of the genus. This placement implies that Caenocentron was in South America far earlier than previously inferred, likely by the late Oligocene. Caenocentron roosevelt sp. nov. is distinguished by the following combination of characters: the absence of a setose ventral projection on the coxopodite (present in all other congeners), the presence of apical lobes on tergum IX (reduced in other species), paired digitate lobes beneath the posterior margin of tergum IX (otherwise found only in one Nearctic species), and a distinct line of robust setae along the apical projection of the coxopodite (absent in other species). Additionally, a key to the males of all 10 currently recognized species of Caenocentron is provided.